1994
DOI: 10.1183/09031936.94.07030467
|View full text |Cite
|
Sign up to set email alerts
|

Reduced endogenous nitric oxide in the exhaled air of smokers and hypertensives

Abstract: R Re ed du uc ce ed d e en nd do og ge en no ou us s n ni it tr ri ic c o ox xi id de e i in n t th he e e ex xh ha al le ed d a ai ir r o of f s sm mo ok ke er rs s a an nd d h hy yp pe er rt te en ns si iv ve es s ABSTRACT: We wanted to determine whether the production of endogenous nitric oxide (NO) is affected by cigarette smoking and various pathological conditions. Endogenously produced NO was measured by chemiluminescence in the exhaled air of 81 healthy volunteers (21 nonsmoking females (NSF), 12 smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 11 publications
3
94
1
3
Order By: Relevance
“…However, the patients exhibited a higher initial level of serum nitrite/nitrate relative to the same controls. With the exception of one report documenting that five patients showed no change in the expired levels of NO 1 h after beginning haemodialysis, 16 this is the first study to analyse changes in expired NO in uraemic patients before and after dialysis.…”
Section: Discussionmentioning
confidence: 86%
“…However, the patients exhibited a higher initial level of serum nitrite/nitrate relative to the same controls. With the exception of one report documenting that five patients showed no change in the expired levels of NO 1 h after beginning haemodialysis, 16 this is the first study to analyse changes in expired NO in uraemic patients before and after dialysis.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, during a single VC exhalation into the reservoir when the first contaminated portion of the air was discarded, the mean(±SEM) NO levels in the remaining part of the exhaled air were in good agreement: 8.1±3.3 ppb [36], and 8.4±1.2 ppb [9]. Inert material, such as polyethylene or NO-impermeable Mylar, should be used for collection [9,35,44,45].…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…certain proinflammatory cytokines and bacterial products) may be present in increased amounts in inflamed/ infected tissues. SCHILLING et al [55] reported reduced exhaled NO in patients with hypertension.…”
Section: Other Diseases Of the Respiratory Tractmentioning
confidence: 99%